T Follicular Helper Cells and B Cell Dysfunction in Aging and HIV-1 Infection - Pallikkuth, Suresh; de Armas, Lesley; Rinaldi, Stefano; Pahwa, Savita (Frontiers in Immunology, 2017)
T follicular helper (Tfh) cells are a subset of CD4 T cells that provide critical signals to antigen-primed B cells in germinal centers (GC) to undergo proliferation, isotype switching, and somatic hypermutation to generate long lived plasma cells and memory B cells during an immune response. The quantity and quality of Tfh cells therefore must be tightly controlled to prevent immune dysfunction in the form of autoimmunity and, on the other hand, immune deficiency. Both Tfh and B cell perturbations appear during HIV infection resulting in impaired antibody responses to vaccines such as seasonal trivalent influenza vaccine, also seen in biologic aging. Although many of the HIV-associated defects improve with antiretroviral therapy (ART), excess immune activation and antigen specific B and T cell responses including Tfh function are still impaired in virologically controlled HIV infected persons on ART. Interestingly, HIV infected individuals experience increased risk of age-associated pathologies. This review will discuss Tfh and B cell dysfunction in HIV infection and highlight the impact of chronic HIV infection and aging on Tfh-B cell interactions.